Elevating Creativity and Criticality Through Game-Based Futuring: An action research case study in futures studies - Balcom Raleigh, Nicolas (My University, 2017)
To address humanity’s greatest challenges, futures studies practices are needed which can break through the trappings of present-day understandings. Combining criticality, challenging assumptions and questioning the present and future, and creativity, producing novel solutions and ways forward, holds potential for reaching beyond the limits of understanding in groups. Game-based futuring, using games to explore possible futures, is a viable approach for elevating creativity and criticality in groups. This thesis develops a role-based futuring game rooted in an experimental Causal Layered Analysis (CLA) Game produced by Sirkka Heinonen and Sohail Inayatullah in 2015. The game developed in this thesis, Metaphor Molecule, aims to elevate creativity and criticality in participatory contexts. It uses 100 percent renewable energy Neo-Carbon Energy scenarios as its content. The theoretical framework for this research combines concepts from creativity, critical futures studies, Causal Layered Analysis, leverage points in systems, and metaphors. Together, this framework serves as the engine for the Metaphor Molecule game: Transforming metaphors can be leverage points in a system of roles. Key game components to metaphor molecule are scenarios, roles, metaphor atoms, and metaphor molecules. The metaphor atoms and metaphor molecules are unique to this game while the concept of scenarios and roles are borrowed from the experimental CLA Game and customized. Metaphor Molecules enable participants to see relationships among the roles as a system. From this vantage point, they then transform metaphors to modify the system. Taking an action research approach, two iterations of Metaphor Molecule are held. Both have similar phases of play with an emphasis on metaphor transformations. Data is collected through triangulation, allowing for an analysis of the game from three sources: pre- and post-game questionnaires; game artifacts; and group interviews. The data is analyzed against the theory to explain and detect elevations in creativity and criticality. Both iterations were found to elevate creativity and criticality, but in different ways and for different reasons. This research demonstrates how a futuring game can be developed in a practical yet rigorous way using action research. The resulting futuring game could be used to explore any set of scenarios and could possibly be used for visioning, Futures Workshops, or other futuring methods. This research demonstrates how futuring games can be developed in a practical yet rigorous way using action research and offers insights into how creativity and criticality are interrelated in participatory futures research.